2018
DOI: 10.9734/jsrr/2018/43782
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nutrition Knowledge among University Students in Ankara

Abstract: Aims: Nutrition knowledge is one of the factors that could influence a university student's nutritional behaviours. This research was aimed to determined nutrition knowledge of university students in Ankara Study Design: The study was conducted in Ankara, Turkey between May and July, 2014 in university students. Place and Duration of Study: This was a cross sectional study. Methodology: Out of 341 students, 66.3% were female (n=226), 33.7% were male (n=115). Our questionnaire included a demographic section, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The study found a high overall internal and test-retest reliability. Other NK questionnaires were also validated and used in students from Turkey (5,19,20) , USA (20) , China (21) and Australia (22) .…”
Section: Discussionmentioning
confidence: 99%
“…The study found a high overall internal and test-retest reliability. Other NK questionnaires were also validated and used in students from Turkey (5,19,20) , USA (20) , China (21) and Australia (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Non-nutrition 40 ( 27) 70 ( 46 Ozdogan et al also showed a higher mean nutritional knowledge score of female students (16.61 ± 4.34) than male students (14.20 ± 5.50) which were statistically significant (P = 0.00) (19). Some studies (22,23) also indicated a higher score for female students (mean score = 27.1 and 58.6 ± 12.8) than for male students (mean score = 26.2 and 54.1 ± 13.3) (P < 0.01) (22,23).…”
Section: Discussionmentioning
confidence: 90%
“…Ozdogan et al conducted a cross-sectional study in Ankara, Turkey, to assess the nutritional knowledge of university students (19). A total of 341 students participated, 33.7% (n = 115) and 66.3% (n = 226) of whom were male and female, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of the students participating in the research had a BMI of ≥25, while 10% had a BMI of <18.5. In other studies conducted with university students, the ratio of those with BMI ≥25 ranged from approximately 9% to 30% (Özdoğan, Yardımcı, Özçelik & Sürücüoğlu, 2012;Yılmaz et al, 2014;Akça & Selen, 2015;Downes, 2015;Abraham, Noriega & Shin 2018). In a health assessment study by the American College Health Association (2011), approximately 20% of university students were determined to be overweight while 10% were obese (American College Health Association World Health Organization [ACHA], 2019).…”
Section: Discussionmentioning
confidence: 99%